Preparation and characterization of bis(μ-1,2-diaminoethane)cobalt(ii) hexavanadate: A layered polyoxovanadate pillared by a cobalt coordination complex - Bunlawee Yotnoi (2018)
The first example of polyoxovanadate layered framework with a cobalt coordination complex as a pillaring unit, CoII(μ-C2N2H8)2[V4IVV2VO14], was readily synthesized under hydrothermal conditions. The structure can be solved and refined in monoclinic P21/n with a = 9.143(3) Å, b = 6.5034(11) Å, c = 15.874(4) Å, β = 101.90(2), V = 923.6(4) Å3and Z = 2. The crystal structure comprises two-dimensional {V4IVV2VO14}2-layers extending parallel to [101], constructed from tetrahedral VVO4 and square pyramidal VIVO5 building units. Adjacent layers are linked through the octahedral {CoIIO2(μ-C2N2H8)2} pillars, within which the CoIIresides on an inversion center. The structure displays N-H•••O and C-H•••O hydrogen bonding between the ethylenediamine and vanadium oxide layers. © 2009 Springer Science+Business Media, LLC.